The impact of trauma of the mucous membrane of the nasal septum in rats on behavioral responses and changes in the balance of the autonomic nervous system (pilot study). (August 2020) - Kastyro, I V; Inozemtsev, A N; Shmaevsky, P E; Khamidullin, G V; Torshin, V I; Kovalenko, N; Pryanikov, P D; Guseinov, I I
Abstract: The nasal cavity surgery are usually traumatic surgery. Septoplasty leads to reactive inflammation, edema and hypoxemia. In the present study, we study the response of the autonomic nervous system (ANS), its role in changing behavioral reactions, as well as possible mechanisms of impairment of cognitive and adaptive reactions in rats after trauma to the nasal septum mucosa. The nasal septum mucosa was scarified in 10 adult mongrel male rats. The day before surgery and 2 days after surgery animals were tested in the square-shaped "open field" (OF) and electrocardiogram (ECG) in 1 hour before OF. ANS condition was analyzed by the high-frequency component of the heart rate (HF) and the low-frequency component of the heart rate (LF). The correlation of HF & LF with rat behavior in the open field before and after surgery was performed. Simulation of septoplasty in rats provokes a powerful stress response in the form of a sharp imbalance of ANS towards its PNS on the 2 postoperative day. Changes in behavioral and research reactions of rats in OF are manifested in a decrease in research activity, a display of uneasiness, depression-like state, as well as anxiety.